Natural Area Weeds: Skunkvine (Paederia foetida) - Stephen F. Enloe; Stephen C. Marble; Kenneth A. Langeland (EDIS)
This 4-page document provides information on the characteristics and control of skunkvine. Written by S. F. Enloe, S. C. Marble, and K. A. Langeland, and published by the Agronomy Department, November 2019.